2014
DOI: 10.1016/j.jinorgbio.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic properties of VO(dmpp)2 as assessed by in vitro and in vivo studies in type 2 diabetic GK rats

Abstract: The bis(1,2-dimethyl-3-hydroxy-4-pyridinonato)oxidovanadium(IV), VO(dmpp) 2 , has shown anti-diabetic effects by in vitro studies in Wistar (W) rat adipocytes and in vivo in obese Zucker rats. The aim of this work is to confirm the therapeutic properties of VO(dmpp) 2 in non-obese type 2 diabetic Goto-Kakizaki (GK) rats. An in vivo study was carried out, treating W and GK rats during 21 days with a daily dose of VO(dmpp) 2 (44 μmol/kg). It was shown that VO(dmpp) 2 doesn't affect the normal increase of body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 77 publications
(144 reference statements)
1
17
0
Order By: Relevance
“…This possibility was confirmed for e.g. BMOV [194] 22 and for V IV O(dhp) 2 24 [195]. As discussed in many publications, vanadium compounds activate numerous signaling pathways and transcription factors.…”
Section: Insulin-like Effects Of Vanadium Compoundssupporting
confidence: 55%
“…This possibility was confirmed for e.g. BMOV [194] 22 and for V IV O(dhp) 2 24 [195]. As discussed in many publications, vanadium compounds activate numerous signaling pathways and transcription factors.…”
Section: Insulin-like Effects Of Vanadium Compoundssupporting
confidence: 55%
“…In 1985, inorganic salts such as NaVO 3 and VOSO 4 were considered again for the treatment of diabetes, but these inorganic salts presented several problems, such as, gastrointestinal distress and low absorption. For this reason, further studies with inorganic salts of vanadium were discarded and newer researches were made towards the complexation of V(IV)O with bidentate organic ligands such as maltolato [146][147][148], dmpp (1,2-dimethyl-3-hydroxy-4-pyridino nate) [149][150][151] and picolinate [148,152] with special attention for the later one, since picolinic acid is the intermediate metabolite of tryptophan and it is therefore less toxic to mammals organism promoting as well the absorption of various metals in the small intestine [153]. The chelating effect of the carrier ligand greatly influences the efficiency of the compound because determines the re-adsorption and improves the biodistribution, stability and tolerability of the metal ion in the organism [5,24,96].…”
Section: Bioinorganic Implication and Application Of Vanadium Complexesmentioning
confidence: 99%
“…The V IV O(dmpp) 2 (bis(1,2-dimethyl-3-hydroxy-4-pyridinonate)oxovanadium (IV)) complex has exhibited antidiabetic activity increasing glucose uptake in adipocytes promoting the phosphorylation of the Akt1, a key protein in insulin signaling [149]. A chronic in vivo treatment in with V IV O(dmpp) 2 decreases hyperglycemia and improves glucose tolerance [151]. Fig.…”
Section: Bioinorganic Implication and Application Of Vanadium Complexesmentioning
confidence: 99%
“…These include their ability to improve glucose homeostasis and insulin resistance in animal models of type 1 and type 2 diabetes mellitus [34][35][36][37][38][39][40][41]. It has been demonstrated that diaqua-(4-chloro-2,5-dipicolinato)oxidovanadium(IV) (VOdipicCl, [V IV O(dipic-Cl)(H 2 O) 2 ]) complex alleviated lipid abnormalities in streptozotocin(STZ)-induced diabetic rats [42][43][44].…”
Section: Introductionmentioning
confidence: 99%